Dendrimer-Dye Assemblies as Templates for the Formation of Gold Nanostructures - Düring, Jasmin; Alex, Wiebke; Zika, Alexander; Branscheid, Robert; Spiecker, Erdmann; Gröhn, Franziska (Macromolecules, 2017)
Dendrimer–dye assemblies are used as novel supramolecular nanoreactors for the formation of various gold nanostructures. The organic–inorganic hybrid systems are investigated with dynamic light scattering, UV–vis spectroscopy, and transmission electron microscopy (TEM) as well as cryo-TEM and high-resolution TEM (HRTEM). We show that the shape of the hybrid assemblies is determined by the choice and the ratio of the building blocks. Shape and size of the gold nanoparticles within the assemblies are controlled by the reducing agent. The accessible range of gold morphologies extends from small and spherical, over ellipsoidal, faceted, and large to highly anisotropic. The approach may open the way to new hybrid systems with applications in catalysis or in the biomedical field.

Formation of CdS in Supramolecular Dendrimer-Dye Assemblies: Electrostatic and Electrostatic-Coordination Templating - Düring, Jasmin; Butz, Benjamin; Spiecker, Erdmann; Gröhn, Franziska (Macromolecules, 2015)
A novel concept for the formation of organic inorganic hybrid nanostructures based on a tunable supra-molecular templating mechanism involving several types of noncovalent interactions is presented. Different organic inorganic hybrid structures with narrow size distributions composed of a cationic dendrimer, an oppositely charged divalent diazo dye, and CdS can be created: First, larger supramolecular structures consisting of several 100 to 1000 dendrimers is built based on ionic and pi-pi interaction. Second, with this self-assembled template, the hybrid nanostructure forms based on electrostatics and coordination interaction. The influence on shape and internal structure of the supramolecular hybrid architectures was investigated. A size control of the assemblies is possible in a range of 60-420 nm. The prospect to direct self-assembly and templating through the controlled combination of different noncovalent interactions potentially allows to create tailor-made systems for various applications.

Porphyrin microneedles-structure control and catalytic activity - Düring, Jasmin; Haschke, Sandra; Bachmann, Julien; Gröhn, Franziska (Colloid and Polymer Science, 2018)
The formation of a novel porphyrin colloidal structure has been investigated-so called microneedles. The porphyrin colloids consist of the tetravalent anionic tetra-(4-sulfonatophenyl)porphyrin (TPPS) and the tetravalent cationic tetra-(N-methyl-4-pyridyl)porphyrin (TMPyP), forming ionic organic solid particles in ethanol. The structure dependence on various influences such as ratio of TMPyP to TPPS, the time of mixing, different solvent mixtures, and the metalation of one porphyrin is investigated with UV-Vis spectroscopy, zeta-potential, light microscopy, and transmission electron microscopy (TEM). The light harvesting potential of the microneedles is demonstrated as a proof of concept by the catalytic degradation of Rose Bengal.
Keywords: Electrostatic self-assembly; Self-assembly; Porphyrin; Organic crystal; Catalysis

Porphyrins as Multifunctional Interconnects in Networks of ZnO Nanoparticles and their Application in Dye-Sensitized Solar Cells - Düring, Jasmin; Kunzmann, Andreas; Killian, Manuela; Costa, Ruben Dario; Guldi, Dirk Michael; Gröhn, Franziska (Chemphotochem, 2018)
ZnO nanoparticles of 2.6 to 4.0 nm in size were interconnected by meso-tetra(4-carboxyphenyl)porphyrin (TCPP) for the realization of novel ZnO–TCPP networks, reaching lateral dimensions ranging from 50 to 800 nm. The resulting ZnO–TCPP networks were probed by dynamic light-scattering experiments, transmission electron microscopy, and spectroscopy, and were also tested as photoactive top layers in TiO2 and ZnO dye-sensitized solar cells (DSSCs). Control over these ZnO–TCPP networks on top of the semiconductor electrodes enables efficiency increases of 10 % and 46 % for TiO2- and ZnO-based photoelectrodes, respectively. In other words, effects, such as reducing the electron recombination and increasing the electron lifetime, document the benefits of using tailored functional hybrid systems in DSSCs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: dye-sensitized solar cells; electron transfer; hybrid assemblies; porphyrins; semiconductor nanoparticles

Self-assembly of supramolecular architectures and polymers by orthogonal metal complexation and hydrogen-bonding motifs - Grimm, Felix; Ulm, Nadine; Gröhn, Franziska; Düring, Jasmin; Hirsch, Andreas (Chemistry - A European Journal, 2011)
A modular construction kit with two orthogonal noncovalent binding sites for self-assembly of supramolecular architectures is presented. The heteroditopic building blocks contain a terpyridine (tpy) unit for coordination of metal ions and a Hamilton receptor for multiple H-bonding of cyanuric acid derivatives. The association constants of ligand binding of M complexes (M=Ru, Zn, Fe, and Pt) with a dendritic end cap were determined to be in the range of 10 and 10 L mol in chloroform. The capabilities for binding of metal ions were investigated by H NMR and UV/Vis spectroscopy. The Fe complexes are most appropriate for the generation of discrete and high-ordered architectures due to their strong tendency to form FeL complexes. Superstructures are readily formed in a one-pot procedure at room temperature. No mutual interactions between the orthogonal binding motifs were observed, and this demonstrates the highly specific nature of each binding process. Decomplexation experiments were carried out to examine the reversibility of Fe-tpy coordination. Substitution of the terminal end cap with a homoditopic bis-cyanurate linkage leads to formation of an iron-containing supramolecular strand. Formation of coordination polymers was confirmed by viscosity measurements. The supramolecular polymer strands can be reversibly cleaved by addition of a terminating cyanuric acid building block, and this proves the dynamic nature of this noncovalent polymerization process. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Tunable Photocatalytic Activity of PEO-Stabilized ZnO-Polyoxometalate Nanostructures in Aqueous Solution - Bernhardt, Sarah; Düring, Jasmin; Haschke, Sandra; Barr, Maissa; Stiegler, Lisa; Schühle, Patrick; Bachmann, Julien; Hirsch, Andreas; Gröhn, Franziska (Advanced Materials Interfaces, 2021)
The photocatalytic activity and selectivity of novel binary and ternary composite nanostructures from polyethylene oxide-stabilized zinc oxide (PEO-ZnO) with and without polyoxometalate (H-4[Si(W3O10)(4)], POM) are determined in aqueous solution under UV-light. Mono- and di-COOH-end-functionalized PEO polymers are used as surface modifiers, influencing the morphology and stability of the ZnO nanoparticles being synthesized in water. POM acts as an additional versatile photocatalytically active building block resulting in a ternary hybrid structure with tunable photocatalytic activity. Catalytic selectivity is demonstrated by studying photocatalytic dye degradations as model reactions, where the chemical backbone of the dyes and their charge turn out to be the basis for the selectivity. All samples are characterized with dynamic light scattering, transmission electron microscopy, scanning electron microscopy, light microscopy, and zeta-potential measurements. With the functionalized PEOs, large ZnO clusters consisting of leaves are formed while 2-[2-(2-methoxyethoxy) ethoxy] acetic acid (TODA) yields ZnO flower-like structures.
CRIS-Team WoS Importer:2021-07-09